Berkaca Penegakan Hukum Islam Di Turki - Asmawi HM (Pena Islam Jurnal Pendidikan Agama Islam, 2019)
This article aims to review discusses the History Turki Usmani Empire, From its appearance, Progress and decline. This article Also aims to discuss Law enforcement in Turkey. with historical descriptive approach, this articledivides the phases of Turki Usmani Empire History of Being five phases Accompanied WITH Execution of Justice in each of these phases